An intracellular diamine oxidase triggered hyperpolarized 129Xe magnetic resonance biosensor. Issue 97 (6th November 2018) - Zhang, Bin; Guo, Qianni; Luo, Qing; Zhang, Xiaoxiao; Zeng, QingBin; Zhao, Longhui; Yuan, Yaping; Jiang, Weiping; Yang, Yunhuang; Liu, Maili; Ye, Chaohui; Zhou, Xin
Abstract : After an enzymatic reaction, the 129 Xe-MRI signal in CB6 lit up. Abstract : Here, a novel method was developed for suppressing 129 Xe signals in cucurbit[6]uril (CB6) until the trigger is activated by a specific enzyme. Due to its noncovalent interactions with amino-groups and CB6, putrescine dihydrochloride (Put) was chosen for blocking interactions between 129 Xe and CB6. Upon adding diamine oxidase (DAO), Put was released from CB6 and a 129 Xe@CB6 Hyper-CEST signal emerged. This proposed 129 Xe biosensor was then tested in small intestinal villus epithelial cells.